FRI0362 HIGH-DIMENSIONAL MULTIPARAMETRIC CHARACTERIZATION OF THE REGULATORY T CELLS LANDSCAPE IN SPONDYLOARTHRITIS. (June 2019) - Simone, Davide; Brough, India; Chen, Liye; Penkava, Frank; Ridley, Anna; Shi, Hui; Mossawi, Hussein Al; Bowness, Paul
Abstract : Background: The Spondyloarthritides (SpA) are immune-mediated conditions characterised by spinal and joint inflammation. The pathogenic role of Th17 lymphocytes has been shown by multiple studies but few reports exist on the phenotype of regulatory T cells (Tregs) and their role in the course of the disease. Studying Tregs is particularly challenging because of their heterogeneous phenotype and potential plasticity at the site of inflammation. Given the complexity of the Treg landscape, a multi-dimensional approach, including both protein and gene analysis, offers novel mechanistic insights that can be leveraged to develop new treatments. Objectives: 1) To describe the Treg phenotype in SpA patients compared to controls. 2) To identify differential expression of markers, such as trafficking molecules or co-inhibitory molecules, within Tregs at the inflammatory site. 3) To define the gene expression landscape in Tregs in the peripheral blood and synovial fluid in patients with active SpA. Methods: A total of 61 patients with SpA (38 with Ankylosing Spondylitis (AS), 23 with Psoriatic Arthritis (PsA)) and 16 age-matched healthy controls were recruited. Peripheral blood (PB) and paired synovial fluid (SF) mononuclear cells (n=8) were also analyzed. Isolated mononuclear cells were stained with 3 multicolor flow cytometry panels, including a total of 35 surface and intracellular protein markers. Manual gating was done in parallel with unsupervised data analysis using FlowSOM and SPADE. Cells from blood and synovial fluid from three treatment-naive PsA patients were isolated and their RNA sequenced at a single cell level with the 10x Genomics platform. Results: Whereas no major difference in the Treg frequency was observed comparing the PB of SpA patients and healthy controls, in the SF we observed a higher Treg frequency, with a striking prevalence of the memory (CD45RA-) compartment (mean: 11.7 vs 4.7%; p=0.01) and a higher expression of Foxp3 (p=0.04). Trafficking markers demonstrated considerable heterogeneity, as visualized on SPADE analysis, mirroring the classification of T helper cells, but little difference in terms of relative frequency compared to healthy controls. Within the Treg compartment we identified populations of Helios-negative Th17-like cells able to secrete higher levels of IL-17A (mean: 2.8 vs 1.2%; p=0.02) while expressing normal levels of Foxp3; and putative regulatory CD8+ T cells expressing classical Treg features (Foxp3, CTLA4). The analysis of the single cell transcriptomic data confirmed a high degree of heterogeneity, both in the SF and the PB, with consistent findings across patients. Unsupervised clustering identified different subsets that share a core of regulatory transcripts, onto which additional programs are added, including a very distinct Th17-like module. Of note, various Treg subsets express preferentially different co-inhibitory genes, suggesting a functional specialization. Conclusion: High-dimensional immunoprofiling in SpA patients shows normal frequency of Tregs in the PB, but increased Tregs with activated phenotype in the inflammatory site. The presence within the Treg population of Th17-like and CD8+ populations are intriguing preliminary findings that require further evaluation. Preliminary transcriptomic analysis confirms the presence of specialized subsets within the Treg compartment. Disclosure of Interests: Davide Simone: None declared, India Brough: None declared, Liye Chen: None declared, Frank Penkava: None declared, Anna Ridley: None declared, Hui Shi: None declared, Hussein Al Mossawi Grant/research support from: UCB, Paul Bowness Grant/research support from: Merck, GSK, Celgene